Some Analysis on Certain Types of Splicing Systems - Fong, Wan Heng (Liverpool Hope University, 2010)
A mathematical model of a splicing system was firstly developed by Head in 1987. This model is abstractly analyzed in the framework of Formal Language Theory, which is a branch of Applied Discrete Mathematics and Theoretical Computer Science. This model consists of a finite set of initial strings over an alphabet that acts upon a finite set of rules. In this paper, some analysis on certain types of splicing systems namely, nullcontext, uniform, simple and SkH system are presented as propositions and corollaries. Besides, some counterexamples are given to illustrate these relations.